MECHANISMS AND SOURCES OF MANTLE METASOMATISM: MAJOR AND TRACE ELEMENT COMPOSITIONS OF PERIDOTITE XENOLITHS FROM SPITSBERGEN IN THE CONTEXT OF NUMERICAL MODELLING - Ionov D.A.; Bodinier J.-L.; Mukasa S.B.; Zanetti A. (My University, 2002)
Mineral and whole-rock chemical data for peridotite xenoliths in basaltic lavas on Spitsbergen are examined to reassess mechanisms of melt–fluid interaction with peridotites and their relative role versus melt composition in mantle metasomatism. The enrichment patterns in the xenoliths on primitive mantle-normalized diagrams range from Th–La–Ce ‘inflections’ in weakly metasomatized samples (normally without amphibole) to a continuous increase in abundances from Ho to Ce typical for amphibole-bearing xenoliths. Numerical modelling of interaction between depleted peridotites and enriched melts indicates that these patterns do not result from simple mixing of the two end-members but can be explained by chromatographic fractionation during reactive porous melt flow, which produces a variety of enrichment patterns in a single event. Many metasomatized xenoliths have negative high field strength element and Pb anomalies and Sr spikes relative to rare earth elements of similar compatibility, and highly fractionated Nb/Ta and Zr/Hf. Although amphibole precipitation can produce Nb–Ta anomalies, some of these features cannot be attributed to percolation-related fractionation alone and have to be a signature of the initial melt (possibly carbonate rich). In general, chemical and mineralogical fingerprints of a metasomatic medium are strongest near its source (e.g. a vein) whereas element patterns farther in the metasomatic ‘column’ are increasingly controlled by fractionation mechanisms.
Keywords: Spitsbergen; lithospheric mantle; metasomatism; trace elements; theoretical modelling